From Diaspora to Religious Pluralism: African American Judaism in the 20th-Century United States - Edith Bruder (Religions)
The origin of this article lies in the concurrent existence of multiple religious groups in the United States and the interactions between them. This essay examines the dynamics of religious pluralism through the interaction of two religious groups—African Americans and Jews—in the realms of religion, society, and politics. Among the diverse religious groups in the United States, the growing presence of Jews, bolstered by migration from Germany in the 19th century and from Eastern Europe in the 20th century, introduced new traditions and significantly contributed to the development of religious experimentation among African Americans. The phenomenon of African American communities embracing Judaism exemplifies how religious pluralism and diaspora intersect to produce new forms of religious and cultural identity. These communities challenge traditional notions of both Jewishness and African Americanness, demonstrating the fluidity of identity in diasporic contexts.